The Role and Social Impact of the Klampok Sugar Factory, Banjarnegara during the Dutch Colonial Period 1889-1933 - Iskandar (IAIN Madura, 2026)
This study examines the history of Klampok Sugar Factory in Banjarnegara Regency, Central Java. Although the factory has long ceased operations, its historical legacy remains visible in the Purwareja Klampok area. This research aims to investigate the establishment of the Klampok Sugar Factory, analyze its roles and impacts on the local community, and identify the factors that led to its closure. The study employs the historical research method, including topic selection, heuristics, source verification, interpretation, and historiography. Data were collected from colonial archives, historical documents, and relevant scholarly literature. The findings reveal that the Klampok Sugar Factory was established in 1889 as part of the expansion of the colonial sugar industry. The factory played a significant role in local development by creating employment opportunities, supporting the growth of railway transportation for sugar distribution, and contributing to educational development through institutions such as the Europeesche Lagere School (ELS). However, the factory ceased operations in 1933 due to the global economic crisis (the Malaise), which severely affected the sugar industry. This study highlights the factory’s substantial contribution to the social, economic, and infrastructural development of Banjarnegara during the colonial period.